The Endothelial ADMA/NO Pathway in Hypoxia-Related Chronic Respiratory Diseases. (25th February 2014) - Lüneburg, Nicole; Harbaum, Lars; Hennigs, Jan K.
Abstract : Since its discovery, many adhere to the view that asymmetric dimethylarginine (ADMA), as an inhibitor of the synthesis of nitric oxide (NO), contributes to the pathogenesis of various diseases. Particularly, this is evident in disease of the cardiovascular system, in which endothelial dysfunction results in an imbalance between vasoconstriction and vasodilatation. Even if increased ADMA concentrations are closely related to an endothelial dysfunction, several studies pointed to a potential beneficial effect of ADMA, mainly in the context of angioproliferative disease such as cancer and fibrosis. Antiproliferative properties of ADMA independent of NO have been identified in this context. In particular, the regulation of ADMA by its degrading enzyme dimethylarginine dimethylaminohydrolase (DDAH) is the object of many studies. DDAH is discussed as a promising therapeutic target for the indirect regulation of NO. In hypoxia-related chronic respiratory diseases, this controversy discussion of ADMA and DDAH is particularly evident and is therefore subject of this review.